Social Return on Investment (SROI) for Creative Economy of Khao Chakan Community, Khao Chakan District, Sa Kaeo Province - Jankrajangjaeng, ืNoppol; Lakul, Anan (Dhammathas Academic Journal, 2023)
The purposes of this research article were 1) to study the social return on investment (SROI) of the project to improve the quality of life and raise income for people in the grassroots community of Khao Chakan, Sa KaeoProvince, 2) to study the satisfaction towards the quality-of-life development project and to raise income for the people in the grassroots community of Khao Chakan, Sa Kaeo Province. The research conducts according to Mixed Methods. The target group used a purposive selection method. There were 2 groups of consists: 1) 4 local leaders 2) Members of two community enterprises in Khao Chakan: Ban Phon Sawan community enterprises, 25 people, and Ban Santisuk@Khao Chakan community enterprise, 25 people, totaling 54 people. The instruments used for data collection consisted of interview form and satisfaction questionnaire. The research result reveals as follows: 1. Social return on investment (SROI) evaluation of the project has a net present value (NPV) of 85,006 baht, while the social return on investment was 2.27 times, meaning that investment for every 1 baht, the rate of return on investment (IRR) is equal to 7.6%. 2. Analysis results satisfaction with the project Overall, it was at the highest level (x̅ = 4.90, S.D. = 0.78).